1986
DOI: 10.1016/s0022-5347(17)45615-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recurrent Varicocele Anatomy Following Surgery and Percutaneous Balloon Occlusion

Abstract: Venography of 44 recurrent varicoceles in 37 patients demonstrated different anatomical patterns of recurrence in surgical patients (26) compared to those treated by percutaneous balloon occlusion (18). The 3 types of patterns identified included parallel, renal vein and transcrotal collateral pathways. Virtually all surgical recurrences were owing to mid retroperitoneal (27 per cent) or low (inguinal) parallel collaterals (58 per cent). The majority of post-balloon occlusion recurrences were due to either hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
5

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 13 publications
1
61
0
5
Order By: Relevance
“…Failure is Zini usually due to the preservation of the periarterial plexus of fine veins (venae commitantes). Less commonly, failure is due to the presence of parallel inguinal or retroperitoneal collaterals that may exit the testis, bypass the retroperitoneal area and join the internal spermatic vein proximal to the site of ligation (65,66). Cremasteric veins cannot be identified using a retroperitoneal approach and may be a potential site of varicocele recurrence (67).…”
Section: Complications Of Varicocele Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure is Zini usually due to the preservation of the periarterial plexus of fine veins (venae commitantes). Less commonly, failure is due to the presence of parallel inguinal or retroperitoneal collaterals that may exit the testis, bypass the retroperitoneal area and join the internal spermatic vein proximal to the site of ligation (65,66). Cremasteric veins cannot be identified using a retroperitoneal approach and may be a potential site of varicocele recurrence (67).…”
Section: Complications Of Varicocele Repairmentioning
confidence: 99%
“…Cremasteric veins cannot be identified using a retroperitoneal approach and may be a potential site of varicocele recurrence (67). The recurrence rate after balloon occlusion varies from 4% to 11% (62,65,68,69). The microsurgical approach with delivery of the testis lowers the incidence of varicocele recurrence to less than 1% (46).…”
Section: Complications Of Varicocele Repairmentioning
confidence: 99%
“…[40][41][42][43][44] The microsurgical varicocelectomy is considered the "gold standard" because it is associated with the lowest risk of complications (varicocele recurrence, hydrocele formation [fluid collection around the testicle] and testicular atrophy). 41,[45][46][47] We have favoured the microsurgical subinguinal approach because it is associated with a higher success rate (disappearance of varicocele) and a lower complication rate (recurrence rate and hydrocele formation), compared with nonmicrosurgical techniques. 46,48 The subinguinal approach is also associated with less operative and postoperative pain than inguinal approaches.…”
Section: Varicocelectomy: Approachesmentioning
confidence: 99%
“…However, these techniques have a recurrence rate that ranges from 5 to 45% [6, 7]. These recurrences are usually the result of residual venous communications from mid retroperitoneal or low inguinal parallel collaterals [8, 9]. Radiologic embolization techniques are also associated with high recurrence rates ranging from 2 to 64% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although physical examination is most commonly used to detect the presence of a clinical varicocele [1, 13], methods using radiologically documented recurrence after varicocele repair are still controversial [14]. Some authors have reported that selective internal spermatic venography (SISV) is helpful to document varicocele recurrence [8, 9, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%